PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. SINAR SOSRO MEDAN (PRODUKSI THE BOTOL SOSRO) - Dora Linda Sinaga; Ruth Felicia Angelica Pasaribu; Renova Pandiangan; Enjelina Suryani Simarmata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2021)
Sinar Sosro Medan is a company engaged in the production of soft drinks. The company has some problems that need fixing. The first problem was employees’ performance that was not maximal. It could be seen from data sales that were not achieved by employees. The second problem was poor employees’ work discipline that could be seen from the violations committed by employees. The third problem was employees’ inappropriate competency that could be seen from the educational background of employees in several employee divisions. Theory used in this study was the theory of human resource management, which was related to employees’ work discipline, competence and performance. This study aimed at examining and analyzing the influence of work discipline and competence on employees’ performance at PT. Sinar Sosro Medan. The method used in this study was quantitative approach with quantitative descriptive research. The nature of this research was descriptive explanatory. Data collection was done by using questionnaires, interviews and documentation studies. The analytical method used in this study was multiple regression analysis. The population in this study was employees of PT. Sinar Sosro Medan as many as 150 people. Determination of the sample in this study was done by using Slovin formula in which the sample was 110 employees of PT. Sinar Sosro Medan. The results of the study on the hypothesis indicated that work discipline and competence simultaneously or partially had significant effect on employees’ performance, where work discipline and competence affected employees’ performance with a determination coefficient of 0.218. The conclusion of this research was that work discipline and competence simultaneously and partially had positive and significant effect on employees’ performance at PT. Sinar Sosro Medan.